BI-Driven Accounting Analytics in U.S. Healthcare: Enhancing Financial Transparency and Decision-making Support. - Kazi Obaidur Rahman; Fairuz Sadaf Aishwarya; Achhia Khanam; Amir Hamza Akash; Songeta Dhar; Farhan Nasrullah; Md Ashiqur Rahman Khan (Emerging Frontiers Library for The American Journal of Engineering and Technology, 2025)
The U.S. healthcare domain is a complex ecosystem of public and private entities including Medicaid, Medicare, hospital systems, commercial insurers, and pharmaceutical companies, monitored and controlled by multiple federal and state regulators. This sector is undergoing rapid digital transformation, where financial efficiency and accountability are as critical as clinical excellence. Traditional accounting methods often lack real-time visibility, predictive capacity, and integration across healthcare systems. Therefore, Business Intelligence (BI)-driven accounting analytics has emerged as a strategic enabler in improving financial transparency, enhancing decision-making support, maintaining regulatory compliance, minimizing fraud, and optimizing resource allocation. By integrating BI tools with U.S healthcare accounting system, entities can analyze and visualize real-time insights through interactive dashboards, perform predictive analysis to streamline revenue flows, manage cost control, and support strategic decision-making. This study explores the methodological foundations, implementation strategies, and managerial implications of BI-driven accounting analytics in the U.S. healthcare system focusing on financial transparency and data-driven decision-making support for stakeholders like managers, policymakers, and healthcare leaders.